Laser-induced degradation of organophosphorus compounds - Polonca Trebše; Mladen Franko (International Journal of Photoenergy)
The object of our research has been laser-induced photo-oxidation of organophosphorus compounds in aqueous media. A XeCl excimer laser with a pulse energy of up to 150 mJ and wavelength of 308 nm has been used as a light source. The research comprised the influence of irradiation conditions on pesticide degradation (number of laser pulses, pulse energy) and decomposition efficiency. The time between irradiation and sample isolation ranged from 5 min to 24 hrs. Rapid decomposition has been achieved within two hours following the irradiation for the range of concentrations limited by the solubility of pesticide (up to 40 mgL-1). 1 mL samples required less than 120 mJ of total irradiation energy at 308 nm, which was delivered to the sample in time intervals shorter then 1 second when catalysts, such as titanium dioxide and hydrogen peroxide were applied. Similar degradation efficiency was also obtained without the addition of catalysts when higher irradiation energies were used. The compounds detected in the irradiated samples suggest that diazinon is converted directly into 2-isopropyl-4-methyl-6-hydroxypyrimidine without the formation of more toxic diazoxon. This transformation involves oxidation of the sulphur atom to the sulphate anion.